Study of weld hardness of pipes at elevated temperature application in power plants - Sarwar, M. (Trans Tech Publications Ltd, 2014)
This study aims to identify the parameters that affect the quality of weld in achieving the required weld quality in terms of hardness and to establish the relationship between different factors that affect the weld quality. The focus is to study and explore the Welding input parameters for Gas Tungsten Arc Welding (GTAW) of elevated temperature piping used in Power Plants and to predict the Weldâs Hardness on construction sites. The study is based on Design of Experiment (DoE) taking the important parameters into account and analyzing each of them. The data generated through experiments has been validated for the hardness based on input process parameters (welding current, welding voltage, travel speed, welding rod diameter) and the findings from the study revealed that the most important factor influencing the hardness of a Creep-Strength Enhanced Ferritic (CSEF) material welds is the Voltage while other factors have minimum or the least influence for the studied ranges and factors. Â© (2014) Trans Tech Publications, Switzerland.